2021
DOI: 10.3390/antiox10111839
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glutathione Levels Decreased with Cognitive Decline among People with Mild Cognitive Impairment (MCI): A Two-Year Prospective Study

Abstract: Glutathione (GSH) is a major endogenous antioxidant. Several studies have shown GSH redox imbalance and altered GSH levels in Alzheimer’s disease (AD) patients. Early detection is crucial for the outcome of AD. However, whether GSH can serve as a biomarker during the very early-phase of AD, such as mild cognitive impairment (MCI), remains unknown. The current prospective study aimed to examine the longitudinal change in plasma GSH concentration and its influence on cognitive decline in MCI. Overall, 49 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Up to now, lipid peroxidation and many oxidative-stress-related molecules have been detected as differentially expressed in AD brain, urine, and/or CSF compared to controls, such as 3-nitrotyrosine, 4-hydroxynonenal, and 8-hydroxy-2-deoxyguanosine [ 161 , 162 ]. Recently, blood has also been considered a source for oxidative-stress-based biomarkers, and Table 1 summarizes the main findings [ 10 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, lipid peroxidation and many oxidative-stress-related molecules have been detected as differentially expressed in AD brain, urine, and/or CSF compared to controls, such as 3-nitrotyrosine, 4-hydroxynonenal, and 8-hydroxy-2-deoxyguanosine [ 161 , 162 ]. Recently, blood has also been considered a source for oxidative-stress-based biomarkers, and Table 1 summarizes the main findings [ 10 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione (GSH), a tripeptide composed of cysteine, glutamate, and glycine, represents the most abundant and dominant endogenous antioxidant in the body; its homeostasis has been reported to be dysregulated in neurodegenerative diseases [ 177 ]. Regarding AD, while serum GSH levels are significantly lower in patients than controls, its plasma concentration has been correlated with cognitive decline, and it is able to discriminate between MCI subjects and healthy volunteers [ 163 , 164 ]. Despite these data, L-cysteine prodrug supplementation, or oral γ-glutamylcysteine administration, did not prevent AD alterations, nor did it restore GSH and oxidative markers, thus underscoring the need for further studies [ 178 ].…”
Section: Resultsmentioning
confidence: 99%
“…Determining cysteinet deregulation in clinical samples from complex neurodegenerative disorders is technically challenging. However, a recent prospective study has shown that plasma GSH concentrations and mental function decreased after two years in patients with mild cognitive impairment (MCI) [ 436 ]. The redox status of human serum albumin, the major protein in the blood, seems to play a predominant role in redox regulation through its thiol group in the redox-sensitive Cys34 [ 437 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Glutathione (GSH) is a predominant antioxidant inside mammalian cells and peripheral blood, with a significant function in oxidative damage protection of neuronal cells. Several studies have indicated an imbalance in GSH redox and altered GSH levels as AD pathology [ 24 ]. In this study, PC-12 cells were treated with oxidative inducers (200 µM H 2 O 2 or 10 µM Aβ 1–42 ) and fruit extracts at different concentrations (25, 50, 100 and 150 µg/mL) for 48 h before measuring GSH level to examine the neuroprotective effect of selected fruit extracts against oxidative damage.…”
Section: Resultsmentioning
confidence: 99%